Solar Water Distiller Using Msp Exp-430 G2 And Msp 430 Launchpad - Mrs.K.Janaki, Su.Ariharaa, V.Nithish, D.S.Rohith Kumar (International Journal of Modern Agriculture, 2021)
Distillation is the process that eliminates rottenness and foreign substances to create unadulterated water from accessible waste water. Various methods are available to distill waste water. The sand filtration framework is examined in this paper. Sand filtration based refining arrangement is exceptionally basic. It utilizes rocks, sand and coconut scrub which are easily available. The excellence of the Solar Water Purifier lies in its simplicity. Our main objective is to automate the entire purification process. Also, we are adding a water monitoring system to monitor the quality of the purified water. The results will be displayed on a web page using IoT technologies. Scaling it into a long-term project to meet a huge institution's water needs will not require much investment considering the cost of materials utilized and the amount of energy consumed.